Reinforcing Indonesia’s Maritime Identity: Strategic Narratives within the Belt and Road Initiative Framework - Riyanto, Budi; Vadra, Rossabel Mellyana (Institut Komunikasi dan Bisnis LSPR, 2024)
This study examines Indonesia's strategic communication within the framework of the global maritime fulcrum, utilizing the theoretical framework of strategic narratives, which encompasses system, identity, and policy narratives (Miskimmon, O'Loughlin, & Roselle, 2013). This study analyzes how the Global Maritime Fulcrum (GMF) vision is projected to enhance Indonesia's diplomatic standing in the Indo-Pacific region. The findings reveal that system narratives are employed to promote a rules-based order, identity narratives reinforce Indonesia's role as a maritime nation and middle power, while policy narratives support the implementation of the ASEAN Outlook on the Indo-Pacific (AOIP) to foster mutually beneficial regional collaboration. GMF as a strategic narrative is utilized by Indonesia to benefit from the China-initiated Belt and Road Initiative (BRI), while maintaining its strategic autonomy and leadership at the regional level. Additionally, this research also highlights the three stages of strategic narrative: formation, projection, and reception by global audiences. However, the research is limited by the lack of empirical evaluation regarding the effectiveness of these narratives both domestically and internationally. Future research should focus on analyzing stakeholder perceptions at the regional level and domestic public reception of the GMF narrative, as well as exploring deeper utilization of media to maximize global reception.